Flax Harvesting Technologies for Flax Harvesting Machines - V. G. Chernikov; R. A. Rostovtsev; V. Yu. Romanenko (Сельскохозяйственные машины и технологии, 2023)
The technology of flax harvesting  depends  on input impacts, including: flax harvester qualitative characteristics; working body parameters; indicators of working conditions; intervening variables reflecting the dynamic properties of the working bodies and the dynamics of the flax flow input. (Research purpose) To establish patterns and the degree of correlation between the qualitative operation indicators (pulling and deseeding quality, flax line stretching); design parameters; machine dynamic properties and harvesting conditions (height and density of flax stem, field surface, thickness and unevenness of flax straw, etc.). (Materials and methods) Based on system analysis, mathematical models of the technological process of flax harvesting were developed. Information models were introduced for examining the main flax harvesters. (Results and discussion) The paper shows that the most typical indicators of the flax harvester working conditions are the flax stem height l(t), centimeters; the seed pod area a(t), centimeters; and field surface roughness z(t), centimeters. It is found that the quality of operation is determined by the deseeding quality, percentages; the flax straw stretching, times; the location of its apical and root parts, centimeters. The estimated indicators are as follows: the pulling height h(t), centimeters, the vibrations of the combine in the longitudinal-vertical plane Q(t), degrees, the location of the apical part of the flax flaw in front of the stripper. (Conclusions) A hydraulic device was developed to adjust the pulling height from 10 to 40 centimeters, depending on the flax stem. An important reserve for increasing the deseeding quality is the change in the width of the deseeding zone of the Vk harvester, centimeters. For this purpose, a mechanism was created for moving the deseeder against the clamping conveyor, depending on the flax stem height l(t), centimeters.